Photograph of St. Paul's Episcopal Church 1941 Easter Altar
Black and white photograph of church altar. Inscription on back: "St. Paul's Church, 17th and Eye Sts. Bakersfield, Calif. Easter, 1941. Ralph H. Cox, Rector". Printed April 19, 1941, Edwards Camera Exchange, Bakersfield